Réponses

2014-05-30T11:57:13+02:00
A) -15(3-2x)+45
= -45+30x+45
= 30

B) -4(a+b)-2a+50
= -4a-4b-2a+50
= -6a-4b+50

C= (x+3)(4+x)
= 4x+x²+12+3x
= x² +7x+12

D= (y-5)(y+2)
= y
²+2y-5y-10
= y²-3y-10
merci beaucoup !!!
de rien
A= - 15(3 - 2x) + 45
A= - 45 + 30x + 45
A= 30x

B= - 4(a + b) - 2a + 50
B= - 4a - 4b - 2a + 50
B= - 4b - 6a + 50

C= (x + 3)(4 + x)
C= 4x + x² + 12 + 3x
C= x² + 7x + 12

D= (y - 5)(y + 2)
D= y² + 2y - 5y - 10
D= y² - 3y -
  • Utilisateur Brainly
2014-05-30T13:15:35+02:00
A= - 15(3 - 2x) + 45
A= - 45 + 30x + 45
A= 30x

B= - 4(a + b) - 2a + 50
B= - 4a - 4b - 2a + 50
B= - 4b - 6a + 50

C= (x + 3)(4 + x)
C= 4x + x² + 12 + 3x
C= x² + 7x + 12

D= (y - 5)(y + 2)
D= y
² + 2y - 5y - 10
D= y² - 3y - 10